Conformational modulation of Ant-Pro oligomers using chirality alteration of proline residues - Kale, Sangram S.; Kotmale, Amol S.; Dutta, Achintya Kumar; Pal, Sourav; Rajamohanan, P. R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2012)
Structural modulation of Ant-Pro (anthranilic acid-proline) oligomers has been carried out by chirality alteration of the proline residues. The results suggest that the chirality altered oligomers show well-defined helical conformation featuring nine-membered hydrogen bonding interactions - without compromising conformational rigidity.

Helical folding in heterogeneous foldamers without inter-residual backbone hydrogen-bonding - Priya, Gowri; Kotmale, Amol S.; Gawade, Rupesh L.; Mishra, Deepti; Pal, Sourav; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Chemical Communications, 2012)
This communication describes a set of hybrid foldamers that do not feature inter-residual, but intra-residual backbone hydrogen-bonding, yet adopt a preferentially folded conformation displaying right-handed helical architecture. Conformational ordering is apparently due to the combined conformational restrictions imposed by the conformationally restricted individual amino acid residues with which the oligomers are made of.

Multifaceted folding in a foldamer featuring highly cooperative folds - Ramesh, Veera V. E.; Priya, Gowri; Kotmale, Amol S.; Gonnade, Rajesh G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Chemical Communications, 2012)
Herein, we report on the folding pattern observed in a synthetic peptide featuring two highly mutually dependent, yet strikingly dissimilar, closed networks of hydrogen-bonded rings that work in a cumulative fashion to stabilize the entire folded architecture of the peptide. Structural studies unequivocally suggest that disruption of any one of these mutually-dependent hydrogen-bonded networks is deleterious to the stability of the fully folded conformation of the peptide.

Unusual conformational similarity of two peptide folds featuring sulfonamide and carboxamide on the backbone - Vijayadas, Kuruppanthara N.; Davis, Hilda C.; Kotmale, Amol S.; Gawade, Rupesh L.; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Chemical Communications, 2012)
Two folded peptides featuring carboxamide and sulfonamide at the core of the peptide fold have been shown to possess almost similar conformational features, despite the well-known fact that carboxamides and sulfonamides have strikingly different hydrogen-bonding and geometrical preferences.

Carboxamide versus sulfonamide in peptide backbone folding: a case study with a hetero foldamer - Ramesh, Veera V. E.; Kale, Sangram S.; Kotmale, Amol S.; Gawade, Rupesh L.; Puranik, Vedavati G.; Rajamohanan, P. R.; Sanjayan, Gangadhar J. (Organic Letters, 2013)
Strikingly dissimilar hydrogen-bonding patterns have been observed for two sets of closely similar hetero foldamers containing carboxamide and sulfonamides at regular intervals. Although both foldamers maintain conformational ordering, the hydrogen-bonding pattern and backbone helical handedness differ diametrically.

Ester vs. amide on folding: a case study with a 2-residue synthetic peptide - Vijayadas, Kuruppanthara N.; Nair, Roshna V.; Gawade, Rupesh L.; Kotmale, Amol S.; Prabhakaran, Panchami; Gonnade, Rajesh G.; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2013)
Although known for their inferiority as hydrogen-bonding acceptors when compared to amides, esters are often found at the C-terminus of peptides and synthetic oligomers (foldamers), presumably due to the synthetic readiness with which they are obtained using protected peptide coupling, deploying amino acid esters at the C-terminus. When the H-bonding interactions deviate from regularity at the termini, peptide chains tend to ``fray apart''. However, the individual contributions of C-terminal esters in causing peptide chain end-fraying goes often unnoticed, particularly due to diverse competing effects emanating from large peptide chains. Herein, we describe a striking case of a comparison of the individual contributions of C-terminal ester vs. amide carbonyl as a H-bonding acceptor in the folding of a peptide. A simple two-residue peptide fold has been used as a testing case to demonstrate that amide carbonyl is far superior to ester carbonyl in promoting peptide folding, alienating end-fraying. This finding would have a bearing on the fundamental understanding of the individual contributions of stabilizing/destabilizing non-covalent interactions in peptide folding.

Orthanilic acid-promoted reverse turn formation in peptides - Kale, Sangram S.; Priya, Gowri; Kotmale, Amol S.; Gawade, Rupesh L.; Puranik, Vedavati G.; Rajamohanan, P. R.; Sanjayan, Gangadhar J. (Chemical Communications, 2013)
Orthanilic acid (2-aminobenzenesulfonic acid, (S)Ant), an aromatic beta-amino acid, has been shown to be highly useful in inducing a folded conformation in peptides. When incorporated into peptide sequences (Xaa-(S)Ant-Yaa), this rigid aromatic beta-amino acid strongly imparts a reverse-turn conformation to the peptide backbone, featuring robust 11-membered-ring hydrogen-bonding.

Synthetic zipper peptide motif orchestrated via co-operative interplay of hydrogen bonding, aromatic stacking, and backbone chirality - Nair, Roshna V.; Kheria, Sanjeev; Rayavarapu, Suresh; Kotmale, Amol S.; Jagadeesh, Bharatam; Gonnade, Rajesh G.; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Journal of the American Chemical Society, 2013)
Here, we report on a new class of synthetic zipper peptide which assumes its three-dimensional zipper-like structure via a co-operative interplay of hydrogen bonding, aromatic stacking, and backbone chirality. Structural studies carried out in both solid- and solution-state confirmed the zipper-like structural architecture assumed by the synthetic peptide which makes use of unusually remote inter-residual hydrogen-bonding and aromatic stacking interactions to attain its shape. The effect of chirality modulation and the extent of noncovalent forces in the structure stabilization have also been comprehensively explored via single-crystal X-ray diffraction and solution-state NMR studies. The results highlight the utility of noncovalent forces in engineering complex synthetic molecules with intriguing structural architectures.

Formation of a pseudo-beta-hairpin motif utilizing the Ant-Pro reverse turn: consequences of stereochemical reordering - Nair, Roshna V.; Kotmale, Amol S.; Dhokale, Snehal A.; Gawade, Rupesh L.; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2014)
Herein, we report a special case of pseudo-beta-hairpin formation by tetrapetide sequences featuring a two-membered Ant Pro dipeptide motif (Ant = anthranilic acid and Pro = proline) at the loop region. These folded structures uniquely feature the presence of C9- and C17-H-bonding patterns at reverse turn and interstrand regions, respectively. Their hairpin nucleation and folding propensities have been expounded using solution and solid state studies of distinct stereochemically altered sequences.

Probing the folding induction ability of orthanilic acid in peptides: some observations - Roy, Arup; Kotmale, Amol S.; Gawade, Rupesh L.; Puranik, Vedavati G.; Rajamohanan, P. R.; Sanjayan, Gangadhar J. (RSC Advances, 2014)
This paper describes the ability of orthanilic acid (2-aminobenzenesulfonic acid, (S)Ant) to promote folding when introduced in a peptide sequence. Three peptide sequences, containing orthanilic acid (SAnt) with a sulfonamide moiety in the turn segment, have been synthesized in the solution phase using suitable coupling agents, and their structural aspects investigated using NMR and X-ray crystallographic studies. Solid- and solution-state conformational analyses reveal that the peptide sequences containing orthanilic acid in their backbone exist in a folded conformation featuring long-range 15-membered ring H-bonding.

Bile acid hydrazides: gelation, structural, physical and spectroscopic properties - Pore, Vandana S.; Agalave, Sandip G.; Pharande, Shrikant G.; Patil, Prashant A.; Kotmale, Amol S. (New Journal of Chemistry, 2015)
Synthesis and gelation properties of a series of novel bile acid hydrazides are presented. These compounds are found to undergo self-assembly leading to organogelation in certain organic solvents. Compound 1 was found to be the most ``effective'' gelator in this series. The properties of this gel have been thoroughly investigated by conventional methods typical for molecular gel studies. Sol gel transition temperature (T-g) of chloroform gels of compounds 1 and 3 was found to increase with increase in the chain length. Sol-gel transition was probed using the isothermal time test and results show that there is instantaneous increase in both the moduli after shear melting, which suggests that the kinetics of formation of the network was very fast. IR and NMR studies revealed hydrogen bonding between amidic carbonyl in the side chain and hydroxyl groups of cholic acid.

Conformational modulation of peptides using beta-amino benzenesulfonic acid ((S)Ant) - Priya, Gowri; Kotmale, Amol S.; Chakravarty, Debamitra K.; Puranik, Vedavati G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2015)
This communication describes the utility of a conformationally restricted aromatic beta-amino acid (2-aminobenzenesulfonic acid, (S)Ant) inducing various folding interactions in short peptides. Sandwiching (S)Ant between diverse amino acid residues was shown to form robust folded architectures featuring a variety of H-bonded networks, suggesting its utility in inducing peptide folding.

Reversal of H-bonding direction by N-sulfonation in a synthetic reverse-turn peptide motif - Vijayadas, Kuruppanthara N.; Kotmale, Amol S.; Thorat, Shridhar H.; Gonnade, Rajesh G.; Nair, Roshna V.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2015)
This communication depicts an intriguing example of hydrogen-bonding reversal upon introduction of a sulfonamide linkage at the N-terminus of a synthetic reverse-turn peptide motif. The ready availability of two sulfonyl oxygen atoms, as hydrogen-bonding acceptors, combined with the inherent twisted conformation of sulfonamides are seen to act as switches that engage/disengage the hydrogen-bond at the sticky ends/termini.

Role of N-terminal proline in stabilizing the Ant-Pro zipper motif - Kheria, Sanjeev; Nair, Roshna V.; Kotmale, Amol S.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (New Journal of Chemistry, 2015)
Hetero-chiral hybrid peptides of the general sequence (L)alpha beta(D)(n)alpha beta(n) featuring proline (Pro, a constrained alpha-amino acid) and anthranilic acid (Ant, a constrained beta-amino acid) as building blocks, where n = 2, 4 etc., form a three-dimensional zipper-like architecture. These zipper peptides attain stable conformation by balancing the co-operative contribution of two competing non-covalent forces, namely hydrogen bonding and aromatic stacking. However, the selection of the N-terminal residue also stands to be one of the key contributors in stabilising the unusually long-range intramolecular hydrogen bond, featuring 26 atoms in the H-bonded ring observed at the termini. This article deals with the substitution alterations at the N-terminus of the zipper motif and their consequent influences on its structure and stability. In this study, the N-terminal Pro residue of the zipper motif was substituted with a flexible amino acid, alanine, and a constrained acyclic amino acid, 2-aminoisobutyric acid, to investigate the role of N-terminal proline in stabilizing the Ant-Pro zipper motif, and its stabilities were assessed by employing solution-state NMR and restrained MD simulation studies.

3-Aminothiophenecarboxylic acid (3-Atc)-induced folding in peptides - Ingole, Tukaram S.; Kotmale, Amol S.; Gawade, Rupesh L.; Gonnade, Rajesh G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (New Journal of Chemistry, 2016)
This paper describes the consequences of incorporating a constrained heterocyclic aromatic b-amino acid 3-aminothiophenecarboxylic acid (3-Atc) into peptides containing beta-turn forming elements such as Pro-Gly motif and the effect on the secondary structural architecture of the entire peptide backbone. Conformational investigations of oligomers comprising an alpha,beta,alpha peptide sequence were carried out by single-crystal X-ray diffraction, solution-state NMR, nOe-restrained MD simulation and circular dichroism studies. The results suggested that these peptide sequences assume helical architecture. The helical folding in the oligomers was found to be devoid of inter-residual H-bonding, instead found to be stabilized by a co-operative effect of 6-membered H-bonding within the 3-Atc unit and conformational restrictions of individual amino acids in the peptide backbone.

Angiotensin II analogs comprised of pro-amb (gamma-turn scaffold) as angiotensin II type 2 (AT(2)) receptor agonists - Jedhe, Ganesh S.; Kotmale, Amol S.; Rajamohanan, Pattuparambil R.; Pasha, Santosh; Sanjayan, Gangadhar J. (Chemical Communications, 2016)
We describe herein the design, synthesis and conformational investigation of Pro-Amb (proline-3-amino-2-methoxybenzoic acid) incorporated Angiotensin II and its truncated analogues. Solution-state NMR and CD studies suggest gamma-turn-like conformation in Pro-Amb analogs in aqueous solution. Furthermore, Pro-Amb analogs have been shown to act as AT(2) receptor agonists.

Bronsted-acid-mediated divergent reactions of betti bases with indoles: an approach to chromeno[2,3-b]indoles through intramolecular dehydrogenative C2-alkoxylation of indole - Deb, Mohit L.; Pegu, Choitanya Dev; Deka, Bhaskar; Dutta, Prantu; Kotmale, Amol S.; Baruah, Pranjal K. (European Journal of Organic Chemistry, 2016)
Divergent reactions of various 1-(aminoalkyl) naphthols and 2-(aminoalkyl) phenols (commonly known as Betti bases) with indoles under Bronsted acid catalysis is reported. With the reaction strategies, one can efficiently synthesize important indole derivatives such as 3-(alpha,alpha-diarylmethyl)indoles and chromeno[2,3-b]indoles. Furthermore, we disclose here a new C-C bond-cleavage reaction, in which naphthol and phenol behave as leaving groups to produce diarylmethanes. Inexpensive reagents such as p-toluenesulfonic acid monohydrate and molecular iodine are used to catalyze the reactions. No metal catalyst is required. The starting material of the reactions, Betti bases, are easily prepared from a three-component reaction of naphthol/phenol, aldehydes, and secondary amines. The mechanisms for the reactions are established through some control experiments. Quinone methide is the key intermediate for all the reactions reported herein.
Keywords: Betti bases; C-O bond formation; Dearylation; Fused-ring systems; nitrogen heterocycles

Disruption of native beta-turns: consequence of folding competition between native and orthanilic acid proline-based pseudo beta-turn - Ingole, Tukaram S.; Vijayadas, Kuruppanthara N.; Chaitanya, K. N.; Kotmale, Amol S.; Gawade, Rupesh L.; Gonnade, Rajesh G.; Rajamohanan, P. R.; Sanjayan, Gangadhar J. (European Journal of Organic Chemistry, 2016)
Five tetrapeptides comprising beta-turn-forming elements and a pseudo beta-turn (C9 H-bonding) based on an SAntPro (orthanilic acid - proline) motif were designed and synthesized. Their extensive conformational investigation by single-crystal X-ray crystallography, solution-state 2D NMR spectroscopic, and nOe-restrained MD simulation studies revealed the formation of C14 or C9 folding and disruption of the native beta-turn (C10 H-bonding) architecture. The striking difference between the psi(psi(2)) angle of ``i + 2'' residues of native beta-turn and designed peptides suggest that formation of the native beta-turn is not favored. The results suggest that other turn-forming motifs can dramatically modulate the stability of the native beta-turn structure.
Keywords: Conformation analysis; hydrogen bonds; Peptidomimetics; structure elucidation

Residue dependent hydrogen-bonding preferences in orthanilic acid-based short peptide beta-turn motifs - Jedhe, Ganesh S.; Vijayadas, Kuruppanthara N.; Kotmale, Amol S.; Sangtani, Ekta; Shinde, Dinesh R.; Gonnade, Rajesh G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (RSC Advances, 2016)
This communication describes the competition between native beta-turn (C10) and 2-aminobenzenesulfonic acid (SAnt)( orthanilic acid)-based pseudo beta-turn (C11) in their hybrid peptides. Solid-state crystal structure and solution-state NMR studies revealed that C10 and C11 can be simultaneously observed under appropriate conditions. The variable temperature NMR coefficient data suggest that the isolated C11/C14 hydrogen bond is weaker in comparison with the consecutive C10 and C11 turns.

Coumarin-appended stable fluorescent self-complementary quadruple-hydrogen-bonded molecular duplexes - Kheria, Sanjeev; Rayavarapu, Suresh; Kotmale, Amol S.; Shinde, Dinesh R.; Gonnade, Rajesh G.; Sanjayan, Gangadhar J. (Journal of Organic Chemistry, 2017)
In this paper we report a coumarin-conjugated self-assembling system adorned with valuable features such as high duplex stability and a built-in fluorophore, which would augment its application potential. This system forms a highly :stalik molecular duplex in a nonpolar solvent (K-dim > 1.9 X 10(7) M-1 in CDCl3). Due to the fluorescent property of coumarin, these new structural motifs may find potential application in material chemistry and supramolecular chemistry.

Structural insights into the hydrogen-bonding and folding pattern in ant-ant-pro-gly tetrapeptides - Baravkar, Sachin B.; Kotmale, Amol S.; Mobin, Samir R.; Gonnade, Rajesh Ghanshyam; Sanjayan, Gangadhar J. (European Journal of Organic Chemistry, 2017)
In this paper, we provide structural insights into the hydrogen-bonding and folding pattern in Ant-Ant-Pro-Gly tetrapeptides (Ant: anthranilic acid; Pro: proline; and Gly: glycine). Comparison of the C-terminal esters and their amide analogs revealed strikingly different H-bonding networks. Whereas the ester analogs displayed an open structure without terminal H-bonding interactions, the amide analogs showed a completely folded structure. Structural details were revealed by using a combination of X-ray crystal structure studies and NOE-based molecular dynamics (MD) simulation studies.

Three in one: prototropy-free highly stable AADD-type self-complementary quadruple hydrogen-bonded molecular duplexes with built-in fluorophore - Kheria, Sanjeev; Rayavarapu, Suresh; Kotmale, Amol S.; Sanjayan, Gangadhar J. (Chemical Communications, 2017)
This communication reports an effective approach for addressing the prototropy-related problems in heterocycle-based AADD-type self-assembling systems by freezing their hydrogen-bonding codes, by utilizing intramolecular bifurcated hydrogen bonding interactions. Using this strategy, we have also developed a hydroquinone-conjugated AADD-type self-assembling system adorned with three valuable features such as prototropy-free dimerization yielding single duplexes, high duplex stability and a built-in fluorophore, which would augment its application potential. The rational approach used herein to arrest prototropic shift may also find application elsewhere, wherein proton shift-mediated structural changes become a detrimental factor.

Triazine-based highly stable AADD-type self-complementary quadruple hydrogen-bonded systems devoid of prototropy - Kheria, Sanjeev; Rayavarapu, Suresh; Kotmale, Amol S.; Gonnade, Rajesh G.; Sanjayan, Gangadhar J. (Chemistry-A European Journal, 2017)
A new class of 1,3,5-triazine-based quadruple hydrogen-bonded system featuring AADD-type self-complementary arrays has been developed and characterized. This system forms highly stable molecular duplex in non-polar solvent (K-dim > 1.9 x 10(7) M-1 in CDCl3) without prototropy-related issues, raising its prospects for application in supramolecular polymer science.

Conformational studies of Ant-Pro motif-incorporated cyclic peptides: gramicidin S and avellanin - Kotmale, Amol S.; Sangtani, Ekta; Gonnade, Rajesh G.; Sarkar, Dhiman; Burade, Sachin; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (New Journal of Chemistry, 2018)
This paper reports conformational changes observed in cyclic bioactive peptides such as gramicidin S and avellanin upon incorporation of a pseudo-beta (C9) Ant-(D)Pro turn motif in their structural frameworks. Solution-state studies suggested that a synthetic gramicidin S analog exhibits a beta-sheet conformation with C9 and C17 intramolecular hydrogen bonding patterns, while its truncated analog disturbs the beta-sheet conformation. Structural details were obtained using a combination of CD studies, X-ray crystal structure studies and nOe-based MD simulation studies.

Helically structured peptide architecture engineered using dimedone as a rigid organic scaffold - Nadimpally, Krishna C.; Madica, Krishnaprasad; Kotmale, Amol S.; Gonnade, Rajesh G.; Sanjayan, Gangadhar J. (ChemistrySelect, 2018)
This communication reports the use of a rigid organic scaffold to attach two unsymmetrical peptide chains on a single carbon atom. The approach describes the step-by-step attachment of peptide chains to the rigid dimedone template (5,5-dimethyl-1,3-cyclohexanedione) - a molecular scaffold that directs orientation of the peptide helices in a well-defined arrangement via intra-molecular hydrogen bonding. The overall topology of the final molecules was studied using CD spectroscopy which suggested existence of helical architecture.